Analyzing Water-Based Livelihoods in the Mekong River Basin: A Livelihood Framework of the Tonle Sap - Sithirith, Mak; Doma, Dok; Sok, Sao; Bunthoeurn, Mak (ACS Publications, 2024)
The livelihood framework is an essential concept in the development theory. Livelihoods vary among places, cultures, religions, and ethnic groups. A bulk of the literature discusses the livelihoods, but many focus on land-based livelihood frameworks, and a few look into the water-based livelihood system. The increased use of water for increased development and climate change has affected the livelihoods of millions of people. This study examines the water-based livelihood system and how it has been affected by increased development pressure and climate change. In answering this question, the study undertakes the reviews of literature and the case studies of livelihoods in Tonle Sap Lake (TSL). It concludes that the flood pulse of TSL shapes three categories of communities and their livelihoods and assets. Hydropower operations and climate change have altered the flows, volumes, inundation, productivity, and livelihoods. The structures and processes at national, regional, and global levels have influenced the livelihoods and governance of TSL. Further, the regional development programs and cooperation frameworks have impacted the structures and processes, the hydrological regimes, and the livelihoods of local people. These changes have made local communities unable to adapt and resilient to these changes and have forcibly transformed them to resort to non-fishing livelihoods, including agriculture and migration.